2012
DOI: 10.1371/journal.pone.0029912
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal DH-PH Domain of Trio Induces Cell Spreading and Migration by Regulating Lamellipodia Dynamics in a Rac1-Dependent Fashion

Abstract: The guanine-nucleotide exchange factor Trio encodes two DH-PH domains that catalyze nucleotide exchange on Rac1, RhoG and RhoA. The N-terminal DH-PH domain is known to activate Rac1 and RhoG, whereas the C-terminal DH-PH domain can activate RhoA. The current study shows that the N-terminal DH-PH domain, upon expression in HeLa cells, activates Rac1 and RhoG independently from each other. In addition, we show that the flanking SH3 domain binds to the proline-rich region of the C-terminus of Rac1, but not of Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 31 publications
4
49
0
Order By: Relevance
“…1D). The N-terminal GEF domain (GEF1) activates Rac1 and RhoG, whereas the C-terminal GEF domain (GEF2) activates RhoA (Blangy et al, 2000;Debant et al, 1996;van Rijssel et al, 2012a). Using the GEF1 inhibitor ITX3, we showed that the activity of GEF1 is required to maintain endothelial resistance (supplementary material Fig.…”
Section: Trio Controls Endothelial Cell-cell Junction Organization Anmentioning
confidence: 93%
See 1 more Smart Citation
“…1D). The N-terminal GEF domain (GEF1) activates Rac1 and RhoG, whereas the C-terminal GEF domain (GEF2) activates RhoA (Blangy et al, 2000;Debant et al, 1996;van Rijssel et al, 2012a). Using the GEF1 inhibitor ITX3, we showed that the activity of GEF1 is required to maintain endothelial resistance (supplementary material Fig.…”
Section: Trio Controls Endothelial Cell-cell Junction Organization Anmentioning
confidence: 93%
“…S1D). To further test whether Trio activity is involved in the regulation of the barrier function of the endothelium, we rescued the impaired resistance of endothelial cells that expressed shRNAs against Trio (shTrio) by expressing the N-terminus of Trio (TrioN), which includes the GEF1 domain and of which the expression is not targeted by the shRNA (van Rijssel et al, 2012a). The endothelial barrier defect of Trio-deficient cells was readily rescued upon expression of TrioN ( Fig.…”
Section: Trio Controls Endothelial Cell-cell Junction Organization Anmentioning
confidence: 99%
“…GTP-bound Rac1 (Rasrelated botulinum toxin substrate 1) was isolated with biotinylated CRIBpeptide coupled to streptavidin agarose beads during a 30 min incubation at 4°C. 28 Beads were washed four times in 50 mM Tris, pH 7.4, 0.5 mM MgCl 2 , 150 mM NaCl, 1% (v/v) Triton X-100, supplemented with protease and phosphatase inhibitor cocktails (Roche, Woerden, the Netherlands). Rac1 was visualized by western blotting using a mouse-anti-human Rac1 antibody (clone 102, BD bioscience, Breda, the Netherlands).…”
Section: Rac1-gtp Pull-down Assaymentioning
confidence: 99%
“…The main Rho-GEF involved in Rac1-induced docking structures in endothelial cells is TRIO (van Rijssel et al, 2012b). Whereas RhoG is a more potent substrate for TRIO-GEF1 than Rac1 (van Rijssel et al, 2012a;Jaiswal et al, 2013), RhoG is not activated upon TNFa stimulation, whereas Rac1 is (van Rijssel et al, 2013). This shows that TRIO can control Rac1 activation upon receiving stimuli that do not necessarily activate RhoG in endothelial cells.…”
Section: Role Of Rac1 In the Vasculature Endothelial Cellsmentioning
confidence: 99%